Oyster Reef Surfaces in the Central Wadden Sea: Intra-Reef Classification and Comprehensive Statistical Description - Hitzegrad, Jan; Brohmann, Leon; Pfennings, Kai; Hoffmann, Tom K.; Eilrich, Anne K.; Paul, Maike; Welzel, Mario; Schlurmann, Torsten; Aberle, Jochen; Wehrmann, Achim; Goseberg, Nils (Frontiers in Marine Science, 2022)
The Pacific oyster (Magallana gigas) is an invasive species in the Wadden Sea transforming parts of it permanently. M. gigas as an ecosystem engineer builds reef structures that are characterized by highly complex and variable surfaces consisting of densely-packed, sharp-edged individuals connected with cement-like bonds. To investigate the interactions between reef structure, shape and formation on the one and wave as well as tidal currents on the other hand, a currently unavailable understanding of the surface roughness is essential. This work reports on observations of oyster reefs for which first seven new structural classes (Central Reef, Transitional Zone, Cluster I, Cluster II, Patch I, Patch II and Garland) are proposed. For each class, high resolution Digital Elevation Models (DEMs) have been elaborated based on Structure-from-Motion (SfM) photogrammetry and analyzed using spatial statistics. By determining probability density functions (PDFs), vertical porosity distributions, abundances, orientations and second-order structure functions (SSFs), topographical parameters that influence the hydraulic bed roughness have been determined. The results suggest, that by applying the structural classification and their distinct topographical roughness parameters, the oyster reef surfaces can be described appropriately accounting for their complexity. The higher statistical moments of the PDFs, skewness Sk = 0.4 – 2.1 and kurtosis Ku = 2.2 – 11.5, as well as the porosity distribution reveal differences, whereas the total roughness height kt = 103 ± 15 mm and the root-mean-square roughness height krms = 23 ± 5 mm yield similar values across all classes. Further, anisotropic behavior across all structural classes has been confirmed. The provided set of topographical roughness parameters enhances the knowledge of oyster reef surfaces and gives insights into the interactions between biogenic structure and surrounding hydrodynamics. The new intra-reef classification allows for more accurate determination of the overall roughness as well as the population dynamics. Combined with hydraulic measurements, the results can be used to estimate the bed roughness induced by the oyster reef surfaces with implications for associated hydraulic processes, sediment transport as well as effects on larvae distribution.